Semiotic Analysis of Gender Inequality in the Film Series Kretek Girl - Sakinah, Nurul; Muary, Rholand (Jurnal Sains Sosio Humaniora, 2024)
This research aims to carry out a semiotic analysis of gender inequality in the "Gretek Girl" film series. In this context, gender inequality is understood as a visual and narrative representation that depicts differences in roles and characteristics between men and women. The analysis method uses a qualitative approach by utilizing Roland Barthes' semiotic concepts to identify visual and narrative symbols that represent gender inequality in the series. Data was collected through in-depth observation of episodes selected purposively. The research results show that "Cretek Girl" uses various traditional gender symbols and stereotypes in depicting its characters. Women tend to be depicted in roles that are more traditional and related to domestic roles, while men are often presented in more powerful and influential contexts. This representation is reflected in the use of body language, the placement of characters in the frame, and the use of colors that depict existing gender conventions. This research underlines the importance of understanding how audiovisual media can influence people's perceptions of gender, and highlights the need to advocate for gender equality in mass media production. The implications of this research indicate the need for a critique of gender representation in the media as well as a call for further research that integrates other approaches to explore the impact of these representations more comprehensively.